Growth response of Albizzia lebbek (L.) Benth. to arbuscular mycorrhizal fungi, Trichoderma viride and Rhizobium leguminosarum - ASHOK AGGARWAL*, SAPANA SHARMA (Indian Phytopathology, 2010)
The synergistic effect of two arbuscular mycorrhizal (AM) fungi (Glomus mosseae and Acaulospora laevis), plant growth promoting bacteria Rhizobium leguminosarum and Trichoderma viride on plant growth and some physiological parameters in Albizzia lebbek was studied. Dual inoculation of G. mosseae and T.viride was the best combination for increasing leaf area and stomatal conductance. The P content was also high in root (0.35Â±0.04) and shoot (0.28Â±0.03) in addition to chlorophyll in plants inoculated with G. mosseae plus T.viride after 90 days of inoculation under polyhouse conditions.